Immunophenotyping of lymphocyte, monocyte and dendritic cell subsets in normal rhesus macaques by 12-color flow cytometry: Clarification on DC heterogeneity - Autissier, Patrick (2010)
Monitoring changes in rhesus macaque immune cell populations during infectious disease is crucial. The aim of this work was to simultaneously analyze the phenotype of rhesus macaque lymphocyte, monocyte and dendritic cell (DC) subsets using a single 12-color flow cytometry panel. Blood from healthy non-infected rhesus macaques was labeled with a cocktail of 12 antibodies. Data were compared to three smaller lineage specific panels and absolute and relative percentages of cells were compared. Our 12-color panel allows for the identification of the following major subsets: CD4+ and CD8+ T lymphocytes, B lymphocytes, natural killer (NK) cells, natural killer T (NKT) cells, monocyte subsets and four non-overlapping HLA-DR+ Lin- cell subsets: CD34+ hematopoietic stem cells, CD11c− CD123+ plasmacytoid DC, CD11c+ CD16+ and CD11c(−/dim) CD1c+ myeloid DC. The development of a multiparameter flow cytometry panel will allow for simultaneous enumeration of mature lymphocyte, NK cells, monocyte and DC subsets. Studying these major players of the immune system in one panel may give us a broader view of the immune response during SIV infection and the ability to better define the role of each of these individual cell types in the pathogenesis of AIDS.